(untitled) (Gaceta de Ciencias Veterinarias, 2020)
In order to determine the contamination of soils with Toxocara spp. eggs on educational institutions at Barquisimeto city, Lara state, was carried out this research under the exploratory modality with a transversal design, in cathedral parish, on Iribarren municipality, Lara state, Venezuela. The samples for the study were collected from the soil of 10 educational institutions, using the double V technique and their parasitological diagnosis, was carried out through the modified Sloss technique according to the protocol used in the Veterinary Parasitology Research Unit from UCLA. For the statistical analysis, frequencies and percentages were used using the SPSS program version 18.0 for Windows. As a result, the contamination of soils with Toxocara spp. eggs was observed in 90% of the schools evaluated. The courtgrounds, playgrounds, sports fields and orchards belonging to these institutions, were the places that were contaminated with this parasite. The application of an epidemiological surveillance plan and education health for the control and prevention of Toxocara spp. and other intestinal helminths of zoonotic interest that may affect the health of the exposed human being is suggested.